Asia's post-global financial crisis adjustment: A model-based dynamic - Masahiro Kawai; Fan Zhai (Asian Development Bank Institute (ADBI), 2010)
Using a dynamic global general equilibrium model, the paper assesses the short- and medium-term impacts of the global financial crisis on Asian economies and the implications of post-crisis adjustment in emerging East Asia (EEA) for the world economy. The analysis suggests that EEA is unlikely to be severely damaged permanently by the global financial crisis, and a worldwide fiscal stimulus could play an important role in stabilizing the global economy in crisis. EEA's efforts at strengthening regional demand, in conjunction with adopting a more flexible exchange rate regime, will promote more balanced regional growth and facilitate an orderly global rebalancing. However, despite the growing size of EEA in the global economy, the region's growth rebalancing has only modest spillover effects on the rest of the world. EEA can contribute to global growth, but it alone cannot become the sole engine driving post-crisis growth in the world economy.
Keywords: C68; E62; F32; F47; G01; 330; Finanzmarktkrise; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Schwellenländer; Allgemeines Gleichgewicht; Asien